Productive Livelihood For Children On QS. An-Nisa Verse 09 - Yayan Musthofa; Ahmad Musta’in Syafi’i (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
A living became a necessity in domestic life. Most studies of living still revolve around consumptive livelihood (an-nafaqah al-istihlākiyah), because read from an outward point of the texts indicate that living is in the form of food, drink, clothing, food, and domicile. Even though these consumptive details can be productive. Productive livelihood (an-nafaqah al-isti'māliyah) for children has not been so massive discussion among researchers. Some published research on productive living still requires a stronger foothold as a legal backing. From there, researchers want to provide the basic foundation of QS. An-Nisa': 09 as a formalistic legal basis in order to be more effective in taking application actions in the practical realm of each family. With the approach of Islamic legal philosophy, researchers read and study QS. An-Nisa': 09, is the verse relevant as the basic basis for productive livelihood for children? And what are the laws born of it? From this study, the results obtained are 1) this verse is relevant to be used as a basis for the concept of productive livelihood for children. 2) with the approach of Islamic legal philosophy gave conclusion of law a) the necessity of applying productive income for children to families who have knowledge and an established economy; b) be an encouragement for families with knowledge or established economies to manage management towards productive livelihood for children; c) does not apply to those who do not have the capacity of both or one of them. Keywords: productive livelihood, children, QS. An-Nisa’: 09